Evaluación de la gerencia administrativa y académica del Colegio Técnico Lcdo. Alejandro Castro Benítez período lectivo 2009-2010 y propuesta alternativa a la práctica docente orientada al bilingüismo docente y dicente - Llumiquinga Tandazo, Mary Catalina (2014)
Our research was focused on the reality of the school Alejandro Benitez Castro, where they study many young people who belong to sectors very humble, who in their daily struggle after study day have to work in agriculture, and other activities allow him to take a loaf home, but at the present time should not worry about his uniform, nor school supplies, thanks to the investment being made by the President of the Republic Rafael Correa.